A companion to modern African Art - Salami, Gitti; Visonà, Monica Blackmun, 1953- (Chichester, West Sussex : Wiley Blackwell, 2013)
Offering a wealth of perspectives on African modern and Modernist art from the mid-nineteenth century to the present, this new Companion features essays by African, European, and North American authors who assess the work of individual artists as well as exploring broader themes such as discoveries of new technologies and globalization. A pioneering continent-based assessment of modern art and modernity across AfricaIncludes original and previously unpublished fieldwork-based materialFeatures new and complex theoretical arguments about the nature of modernity.
Invisibility Difference Last Word: The Lines of a Future Argument; Notes; References; Part IV: Modernities and Cross-Cultural Encounters in Arts of the Early Twentieth Century; 7'One of the Best Tools for Learning': Rethinking the Role of'Abduh's Fatwa in Egyptian Art History; Introduction; Art, Islam, and the Imam; An Insightful Traveler's Observations;'And They Do Not Spare Any Effort in Preserving These Things'; Al-Suwar wa-l-Tamathil: A Fatwa without Fine Arts; Between the Educational and the Legal; The Fatwa's Five Parts; Conclusion; Notes; References.
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed December 12, 2013).
Keywords: 1800-2099; Art, African -- 20th century; Art, African -- 19th century; Art, African -- 21st century; Art, African; Electronic books